Upaya Guru dalam Melaksanakan Pembelajaran Daring Pada Mata Pelajaran IPS di Sekolah Dasar - Rianti, Nur Amalia; Gusrayani, Diah; Nugraha, Dadan (Jurnal Pena Ilmiah, 2021)
The implementation of physical distancing during Covid-19 pandemic affected on education sector by the presence of online learning. This study aims to be cognizant of teacher’s effort in implementing online learning learning on social studies subjects in grades IV and V SD Ar Rafi’ BHS. The method used in this research is case study with two social studies teachers as subjects. Data collectiontechniquesareby observation, interviews, and documentation. Theresult indicates that the teacher’s effort to implement online learning were adjusting the learning process with RPP. Teachers uses discussion and question-and-answer methods, also they used media such as PPT, PDF, and learning video. Teachers use WhatsApp, Zoom and GoogleMeet applicatioms as their teaching media. Teachers always appreciate how far learning outcomes and activeness of their students. To measure student’s understanding, teachers use Quizizz and Googleform. The results of the learner’s study after the teacher’s effort have average well.